2021
DOI: 10.1186/s12889-021-11840-3
|View full text |Cite
|
Sign up to set email alerts
|

Non Hodgkin lymphoma in Lebanon: a retrospective epidemiological study between 1984 and 2019

Abstract: Background Lymphomas are ranked as the fifth most common cancer in Lebanon. There is concern about the need of information regarding the prevalence of lymphoid neoplasm particularly Non-Hodgkin lymphoma (NHL) subtypes in the Lebanese population. This study intended to establish a descriptive status of NHL histological subtypes distribution in Lebanon thus identifying the most common types, knowing that the literature is poor regarding the distribution of lymphoid malignancies particularly NHLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…In addition, HL shows a gradual decline in cases with age in this series, consistent with what was seen in China [15,16,20,21]. BCL compromised 61.6% of all lymphomas reported in this study, similar to those reported in MENA countries [17,18,22]. However, a greater number was reported in most East Asian countries such as South Korea (72.5%), China (64.4%), Sri Lanka (65.1%), and Thailand (78.3%) [23][24][25][26].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HL shows a gradual decline in cases with age in this series, consistent with what was seen in China [15,16,20,21]. BCL compromised 61.6% of all lymphomas reported in this study, similar to those reported in MENA countries [17,18,22]. However, a greater number was reported in most East Asian countries such as South Korea (72.5%), China (64.4%), Sri Lanka (65.1%), and Thailand (78.3%) [23][24][25][26].…”
Section: Discussionsupporting
confidence: 91%
“…BCL compromised 61.6% of all lymphomas reported in this study, similar to those reported in MENA countries (17,18,20). However, a greater number was reported in most East Asian countries such as South Korea (72.5%), China (64.4%), Sri Lanka (65.1%), and Thailand (78.3%) (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 85%
“…Non-Hodgkin Lymphoma (NHL) comprehends a variety of neoplasm with an origin mostly on B cells (up to 90% of them), and the remaining percentage is represented by T cells and Natural Killer (NK) cells [1,2]. The sites with significant development frequency are the lymph nodes, spleen, and bone marrow [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The sites with significant development frequency are the lymph nodes, spleen, and bone marrow [1,3]. The states related to immunosuppression or autoimmune diseases are key risk factors related to developing NHL [2][3][4][5]. Regarding the presence of NHL on the global panorama, NHL represents an incidence of 2.8% of new cancer cases and 2.6% of deaths worldwide [6].…”
Section: Introductionmentioning
confidence: 99%